Marketing Channel Analysis of Chicken Eggs in Pannampu Market, Tallo District, Makassar City - Asmayanti Asmayanti; Andi Annisa; Azrul Azrul; Marhawati Marhawati; Agus Syam (Universitas Negeri Makassar, 2023)
In general, this research aims to describe the chicken egg marketing channel which includes marketing margins and marketing efficiency. This type of research is included in descriptive research or categorized in qualitative research methods using survey methods, namely describing, explaining and interpreting a phenomenon that occurs in an object and the data is qualitative, namely data that is described in words or sentences according to categories to obtain a conclusion. Source of data used in this research is primary data. The primary data in this study were obtained directly from interviews with several traders in Pannampu Market. The data analysis technique is qualitative, which is done when data collection takes place. In this study, a data reduction process was carried out through the observation process of the marketing channels for chicken eggs in the pannampu market. Then the data analysis was carried out from the presentation of the data obtained during the data collection process. After the analysis process, a conclusion is obtained regarding marketing channels, marketing margins, and marketing efficiency of chicken eggs in the pannampu market. First, from the results of the analysis of the chicken egg marketing channel in the pannampu market, there are two marketing channels. Marketing channel I has the highest total margin of IDR 32,000. The high margins in this marketing channel are due to the presence of shipping costs. Meanwhile, the marketing channel II is the channel with the lowest total margin, namely IDR 22,000. Based on the high and low marketing margins, marketing channel II is the most efficient marketing channel economically. But both marketing channels are all profitable.